PENDAMPINGAN IMPLEMENTASI KURIKULUM MERDEKA BAGI GURU SMP DI KOTA MADIUN - Sudarmiani Sudarmiani; Nurhadji Nugraha; Ibadulah Malawi; Moh. Ayat Efendi; Sutrisni Sutrisni; Eko Sudaryanto (JURNAL PENGABDIAN MANDIRI, 2022)
This program aims to assist junior high school teachers in preparing and implementing an independent curriculum as well as possible. This activity was carried out at SMP N 5 Madiun City, which is located at Madiun City, East Java in February 2022. The target of this service activity is 16 teachers. The implementation of assistance is carried out in accordance with health protocols. Based on the results of the activities that have been carried out, assistance in implementing the Independent Curriculum is very important. The stages of curriculum implementation are not regulations or standards set by the government. This stage is designed to assist educators and educational units in setting targets for the implementation of the Independent Curriculum